In Vitro Antimicrobial Activity of Thymus Vulgaris,Origanum Vulgare and Rosmarinus Officinalis Against Dental Caries Pathogens - B. A. Abdul sattar (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
The in vitro antimicrobial activity of Thymus vulgaris,Origanum vulgare and Rosmarinus officinalis water extracts were studied against Streptococcus mutans, Lactobacillus acidophilus and Candida albicans isolates two of each isolate. All cold water extracts exhibited antimicrobial activity against all tested microorganisms. The largest zone of inhibition was obtained against Candida albicans isolates. Streptococcus mutans isolates and one isolate of Lactobacillus acidophilus showed no effect in 300mg\ml concentration of Thymus vulgaris extract,while the same concentration of Rosmarinus officinalis extract had no effect on all Streptococcus mutans isolates and Lactobacillus acidophilus isolates .Origanum vulgare extract had inhibitory effect in 200mg\ml concentration with (10mm) diameter against all isolates .This study depicts that the extract of Thymus vulgaris,Origanum vulgare and Rosmarinus officinalis extracts possess very good antifungal and antibacterial activities respectively and can be used as a potential source of novel antimicrobial agents used to cure dental caries.